Epistemological problems of prediction in Stochastic and Dynamic General Equilibrium (DSGE) models - Barrientos Apumayta, Enrique Agapito (2022)
This article highlights the impact and criticism of the theoretical assumptions of prediction in the EGDE models, in addition to its scope and limits in terms of economic policy carried out by central banks. We have chosen various topics to explain predictive phenomena in social sciences and mainly in economics, based on econophysics, econometrics and macroeconometrics applied to EGDE models, but they revolve around the mind-brain problem and the “theory of cognition of predictive coding”. We conceptualize their contributions through epistemological problems and relate them to their application to EGDE models. Thus, we intend to emphasize the task of our criticism to open the field of analysis of prediction theories towards complex systems in social sciences and other epistemic debates. Therefore, the thesis of limitations in prediction is defended under the concept of the brain as a prediction engine to give a contribution to a possible epistemological conception of prediction in natural and social sciences.